Left to Murder (An Adele Sharp Mystery-Book Five) - Blake, Pierce (Lukeman Literary, 2020)
"When you think that life cannot get better, Blake Pierce comes up with another masterpiece of thriller and mystery! This book is full of twists and the end brings a surprising revelation. I strongly recommend this book to the permanent library of any reader that enjoys a very well written thriller." --Books and Movie Reviews, Roberto Mattos (re Almost Gone) LEFT TO MURDER is book #5 in a new FBI thriller series by USA Today bestselling author Blake Pierce, whose #1 bestseller Once Gone (Book #1) (a free download) has received over 1,000 five star reviews. A woman is found dead in Bordeaux, murdered against the backdrop of its idyllic wine country, and authorities suspect a connection to a similar murder in Italy-and an active serial killer. FBI Special Agent Adele Sharp, triple agent of the U.S., France and Germany, is called in, the only one with the international expertise-and brilliant mind-to piece it all together. Adele enters the dark canals of the killer's mind, finding clues where others do not, and feels confident she can catch him before he kills again. Until a shocking twist throws all she thought she knew into a tailspin. An action-packed mystery series of international intrigue and riveting suspense, LEFT TO MURDER will have you turning pages late into the night. Book #6-LEFT TO ENVY-is also available!
Keywords: Krimi, detektivky